Implementasi Augmented Reality Pada Media Promosi Penjualan Rumah (Studi Kasus : Berlian Ciater) - Segi Wulandari Wibowo; Hidayatullah Al Islami (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
A decent house to live in doesn't have to be luxurious, but comfortable and according to needs. Berlian Developer is a residential development that is growing rapidly with a focus on developing residential areas with a cozy mini cluster concept, which offers comfortable, environmentally friendly housing in the best locations at affordable prices. In a business, especially in the property sector, the service provider will provide the building designs they have, such as the design of the house down to the interior. Therefore we need a realtime picture that will make it easier to visualize the design of the house building and the interior design of the arrangement, namely by using augmented reality (AR). Augmented Reality is a technology in the field of multimedia that can incorporate one or several 3D objects into a real environment using camera media, Augmented Reality can be applied to Android mobile devices. This study aims to create an application that is useful to make it easier to promote house sales in Berlian Ciater in 3D. For making this design using software Unity, Draw.io and Vuforia.